Perbandingan Ekspor Kopi Indonesia Pada Tahun 2021 Dan 2022 - Febrianti, Kemala Citra; Hamdani, Dani; Rahmani, Julya Nur; Ummah, Rifa Syarifatul; Ramanda, Noviyanti; Wahid, M. Fadly; Ramadhan, Reka (Westscience Press, 2024)
This study aims to gain a deeper understanding of the comparison of the amount of capacity (kg) of Indonesian coffee exports between 2021 and Indonesian coffee exports in 2022. The data used in this study were gathered through library research, which allowed us to collect data from literature related to the object of our research, such as documents or archives containing data on coffee production, coffee plantation area, total capacity (kg) of Indonesian coffee exports, and the behavior of Indonesian coffee prices. The data sources were kindly provided by the Central Bureau of Statistics (BPS) and the Center for Agricultural Data and Information Systems of the Secretariat General, Ministry of Agriculture. In this research, we employed two data analysis techniques: the Shapiro-Wilk normality test and the Wilcoxon test. The results of these tests indicate a comparison between Indonesian coffee exports in 2021 and 2022. This comparison is characterized by a decrease and also an increase in mean rank and sum of rank.